Розроблення дієтичних страв для меню сніданків при готелях - Романюк, Ангеліна Василівна; Пушка, Ольга Сергіївна; Сильчук, Тетяна Анатоліївна (My University, 2022)
Публікація актуалізує питання розширення та удосконалення страв дієтичного призначення для меню сніданків при готелях. На сьогоднішній день цукровий діабет найрозповсюдженіше захворювання в світі, проте в закладах готельно-ресторанного господарства відсутнє харчування для людей хворих на цукровий діабет. Робота містить огляд на основні положення, такі як: що таке цукровий діабет, особливості харчуван-ня при цукровому діабеті, коротка характеристика на цукрозамінники та підсолоджувачі. На основі прове-дених досліджень було встановлено найбільш оптимальні дозування цукрозамінників та підсолоджувачів, і розраховано зміну енергетичної цінності солодких страв за рахунок вилучення легкозасвоюваних вугле-водів. У результаті було розширено асортимент страв діабетичного призначення, які цілком задовольня-ють гастрономічні потреби людей, що страждають на цукровий діабет без потреби відмови від солодких страв. Rational and healthy nutrition is the key to longevity and good health. Organizing the necessary nutritional composition of breakfast, lunch or dinner is especially difficult for people with health problems outside the boundaries of home food. Often, tourists or business people, staying in accommodation, need special food, which is due to the peculiarities of their physiological state. One of these features is represented by the need to exclude easily digestible carbohydrates from the diet. This necessity is due to the fact that today diabetes is a leading disease in all countries of the world. The publication updates the issue of expansion and improvement of dietary dishes for hotel breakfast menus. Almost every hotel guest chooses a sweet dish during the morning meal along with a hot drink, which is unacceptable for people suffering from diabetes. Today, this disease is the most common in the world, but in the hotel and restaurant industry, it is often not taken into account when organizing the diet of people with diabetes. The work presents an overview of the main provisions of diabetes mellitus, features of nutrition during the disease, and gives a brief description of the used sucrose substitutes.
Keywords: кафедра готельно-ресторанної справи; цукровий діабет; цукрозамінники; підсолоджувачі; легкозасвоювані вуглеводи; діабетичне харчування; готельне господарство; diabetes; sugar substitutes; sweeteners; easily digestible carbohydrates; diabetic nutrition; hotel industry